Ионная обработка циркониевой керамики мощными импульсными пучками; Журнал технической физики; Т. 85, вып. 1 - Гынгазов С. А. Сергей Анатольевич; Васильев И. П. Иван Петрович; Суржиков А. П. Анатолий Петрович; Франгульян Т. С. Тамара Семёновна; Чернявский А. В. Александр Викторович (2015, 2015)
Заглавие с экрана